Do channel integration efforts pay-off in terms of online and offline customer loyalty?. Issue 7 (10th July 2017) - Frasquet, Marta; Miquel, Maria-José
Abstract : Purpose: The purpose of this paper is to investigate the effects of multichannel integration (MCI) on customer loyalty. The specific objectives are to provide an appropriate reliable measure of the construct, and to analyse the impact of MCI on offline and online loyalty, both directly and by mediation of customer satisfaction. Design/methodology/approach: The paper focusses on the retail apparel sector of Spain and the UK. The authors applied a scale development process and tested the model with data of 761 multichannel apparel shoppers. The proposed theoretical model was estimated through EQS 6.1 and a mediation test was calculated. Findings: The findings show, first, that the construct of channel integration has two dimensions: reciprocity, which refers to the possibility of crossing the channels while shopping, and coordination, which refers to the alignment of offline and online offers. Second, that MCI affects positively both offline and online loyalty both directly and through satisfaction, which partially mediates the relationship. Research limitations/implications: Culture might play a moderating role in the relationships found that are not analysed. Practical implications: The findings have implications for the managers of multichannel retail companies as they help to understand the benefits of channel integration in creating a loyal customer base both online and offline. Originality/value: This paper contributes to the literature on multichannel retailing in two main ways: first, by developing a scale to measure MCI, and second, by demonstrating that MCI has strong effects on customer satisfaction and loyalty.